A Calpain-Like Protein Is Involved in the Execution Phase of Programmed Cell Death of Entamoeba histolytica - Domínguez-Fernández, Tania; Rodríguez, Mario Alberto; Sánchez Monroy, Virginia; Gómez García, Consuelo; Medel, Olivia; Pérez Ishiwara, David Guillermo (Frontiers in Cellular and Infection Microbiology, 2018)
Oxygen or nitrogen oxidative species and chemical stress induce the programmed cell death (PCD) of Entamoeba histolytica trophozoites. PCD caused by the aminoglycoside G418 is reduced by incubation with the cysteine protease inhibitor E-64; however, no typical caspases or metacaspases have been detected in this parasite. Calpain, a cysteine protease activated by calcium, has been suggested to be part of a specific PCD pathway in this parasite because the specific calpain inhibitor Z-Leu-Leu-Leu-al diminishes the PCD of trophozoites. Here, we predicted the hypothetical 3D structure of a calpain-like protein of E. histolytica and produced specific antibodies against it. We detected the protein in the cytoplasm and near the nucleus. Its expression gradually increased during incubation with G418, with the highest level after 9 h of treatment. In addition, a specific calpain-like siRNA sequence reduced the cell death rate by 65%. All these results support the hypothesis that the calpain-like protein is one of the proteases involved in the execution phase of PCD in E. histolytica. The hypothetical interactome of the calpain-like protein suggests that it may activate or regulate other proteins that probably participate in PCD, including those with EF-hand domains or other calcium-binding sites.